Disentangling the Fairness & Discrimination and Synergy Perspectives on Diversity Climate: Moving the Field Forward. (July 2016) - Dwertmann, David J. G.; Nishii, Lisa H.; van Knippenberg, Daan
We provide a theory-driven review of empirical research in diversity climate to identify a number of problems with the current state of the science as well as a research agenda to move the field forward. The core issues we identify include (a) the fact that diversity climate is typically treated as unidimensional, whereas diversity research would suggest that there are two major perspectives that could be reflected in diversity climate—efforts to ensure equal employment opportunity and the absence of discrimination versus efforts to create synergy from diversity; (b) a tendency to let the level of analysis (individual psychological climate or shared team or organizational climate) be dictated by convenience rather than by careful theoretical consideration, thus sidestepping key issues for research concerning the causes and consequences of the sharedness, or lack thereof, of diversity climate perceptions; and (c) the tendency to include diversity attitudes and other nonclimate elements in climate measures even though they are different from climate both conceptually and in their antecedents and consequences. The research agenda we advance suggests a need both for different operationalizations and for new research questions in diversity climate, diversity, and relational demography research.